2010
DOI: 10.1177/1756283x10365439
|View full text |Cite
|
Sign up to set email alerts
|

Review: Diagnosis and management of Barrett’s esophagus for the endoscopist

Abstract: In Barrett's esophagus, the stratified squamous epithelium lining the esophagus is replaced by specialized intestinal-type columnar epithelium. The prevalence of Barrett's esophagus has ranged from 0.9% to 4.5%. The rate of progression from Barrett's esophagus to esophageal adenocarcinoma is 0.5% per patient-year. Proton-pump inhibitors are the mainstay of symptom control in Barrett's patients. Nondysplastic Barrett's and Barrett's with low-grade dysplasia (LGD) are typically managed by periodic surveillance. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 83 publications
(88 reference statements)
0
26
0
Order By: Relevance
“…In a prospective randomized trial, both "cap-and-snare" and "band-and-snare" technique can provide adequate depth and histological staging and have similar safety profies [176,177]. Studies have demonstrated that EMR is safe and effective for the treatment of superficial lesions for successful eradication of BE with varied degree of dysplasia and IMC [169,178,179]. Five-year follow-up data for 231 BE patients with IMC demonstrated a 95.7% complete response rate [180].…”
Section: Non Ablative Modalities (Endoscopic Resection-emr)mentioning
confidence: 99%
See 2 more Smart Citations
“…In a prospective randomized trial, both "cap-and-snare" and "band-and-snare" technique can provide adequate depth and histological staging and have similar safety profies [176,177]. Studies have demonstrated that EMR is safe and effective for the treatment of superficial lesions for successful eradication of BE with varied degree of dysplasia and IMC [169,178,179]. Five-year follow-up data for 231 BE patients with IMC demonstrated a 95.7% complete response rate [180].…”
Section: Non Ablative Modalities (Endoscopic Resection-emr)mentioning
confidence: 99%
“…Because of that Japanese Society for Gastrointestinal Endoscopy (JSGE) recomended using of EMR only for HGD lesions, involving less than one-third of the circumference of the esophageal wall [179]. Regarding length of BE, recent observational studies reported good results when segments of BE more than 2 cm or flat mucosal lesions can be resected by CBE_EMR [170,172,178]. SRER is mostly limited to a 5-cm Barrett's segment [189].…”
Section: Non Ablative Modalities (Endoscopic Resection-emr)mentioning
confidence: 99%
See 1 more Smart Citation
“…Conservative management, involving symptom control and periodic endoscopic surveillance to exclude progressive disease, is recommended for patients with Barrett’s esophagus without evidence of dysplasia or cancer. Lifestyle modifications can be helpful to increase esophageal acid clearance and decrease the incidence of reflux events [41]. …”
Section: What Do We Know About Unmet Needs?mentioning
confidence: 99%
“…Barrett's esophagus (BE) is a change in the distal esophageal epithelium of any length that can be recognized as columnar‐lined mucosa at endoscopy and is confirmed to have intestinal metaplasia (IM) by biopsy of the tubular esophagus . BE is a precursor for the development of esophageal adenocarcinoma (EAC) via a pathway that begins with goblet‐cell metaplasia, followed by dysplasia and eventually EAC . The risk of progression to EAC in nondysplastic BE is estimated to be 0.12–0.5% per patient per year .…”
Section: Introductionmentioning
confidence: 99%